Vector competence evaluation of mosquitoes for Tahyna virus PJ01 strain, a new Orthobunyavirus in China - Cai, Tong; Liu, Ran; Jiang, Yuting; Jia, Nan; Jian, Xianyi; Cheng, Xiaolan; Song, Fenglin; Guo, Xiaoxia; Zhao, Tongyan (Frontiers in Microbiology, 2023)
Tahyna virus (TAHV), an arbovirus of the genus Orthobunyavirus, is a cause of human diseases and still relatively unknown worldwide. Herein, a novel virus was isolated from Aedes sp. mosquitoes collected in Panjin city, Liaoning province. Phylogenetic analysis revealed that the virus shared high similarity with TAHV, and was named the TAHV PJ01 strain. After oral infection with artificial virus blood meals (1:1 of virus suspension and mouse blood), the virus was detected in the midgut, ovary, salivary gland and saliva of Aedes albopictus, with an extrinsic incubation period of 2 days and a fluctuating increasement of transmission and dissemination rates, indicating Ae. albopictus is an efficient vector. Whereas no virus was detected in the saliva of Culex pipiens pallens. Suckling mice bitten by infectious Ae. albopictus develop obvious neurological symptoms, including inactivity, hind-leg paralysis and difficulty turning over, when the virus titer reached 1.70×105 PFU/mL in the brain. Moreover, Ae. albopictus is also a reservoir host that transmits the virus vertically, which further increases the risk of outbreaks. This study has important epidemiological implications for the surveillance of pathogenic viruses in China and guiding comprehensive vector control strategies to counteract potential outbreaks in future.